Expansion of CD57+ CD8 T cells in common variable immunodeficiency with hepatopathy and CMV infection - Bez, Patrick; Santangeli, Enrico; Goldacker, Sigune; Salzer, Ulrich; Warnatz, Klaus (Frontiers in Immunology, 2025)
BackgroundCommon variable immunodeficiency (CVID) is associated with an altered immune homeostasis affecting many T-cell subpopulations, including an increased proportion of CD57+ CD8 T lymphocytes. This expansion has been associated with the clinical manifestation of granuloma/lymphadenopathy and a positive CMV status. The aim of the study is to describe the prevalence of an expansion of CD57+ CD8 T cells in CVID patients and determine its diagnostic value.MethodsThis is a monocentric retrospective study including 131 patients with a median follow-up of 9 years. The inclusion criteria are a diagnosis of CVID according to European Society for Immunodeficiencies (ESID) criteria and at least two independent assessments of CD57+ CD8 T cells. Patients on immunosuppressive therapy were excluded.ResultsThe expansion of CD57+ CD8 T cells was part of the previously described immune alteration, including altered CD4/CD8 ratio and a decrease in naïve CD4 T cells. The loss of significant association with increasing age might corroborate the suggestion of premature immunosenescence in CVID. Significantly higher values of CD57+ CD8 T cells were seen in patients with a complicated clinical phenotype, and especially associated with the presence of splenomegaly, status post-splenectomy, and hepatic disease. Additionally, patients with a history of CMV infection presented with elevated CD57+ CD8 T cell values. When comparing the potential diagnostic value of expanded CD57+ CD8 T cells compared to alterations in other T-cell subsets in relation to specific complications, we could not identify a single complication in CVID patients for which absolute or relative CD57+ CD8 T cell counts were superior to more commonly used T-cell populations, except for CMV infection.ConclusionThis is the largest study on the prevalence and diagnostic relevance of the expansion of CD57+ CD8 T cells in CVID. Most CD57+ CD8 T cells are part of the CD45RA+ terminal effector subset. While we could not detect an added value of the diagnostic evaluation of CD57+ CD8 T cells at this time, further investigation in circulation and tissue might enhance our understanding of the pathogenesis of hepatic disease and thereby gain novel diagnostic value in the future.